THE USE OF INTERACTIVE MULTIMEDIA IN TEACHING VOCABULARY : A Quasi-Experimental Study of the Seventh Grade Students in One of Junior High School in Bandung - Fitria Sani, - (2011)
This study is aimed at investigating the use of interactive multimedia in teaching vocabulary. It is conducted in attempt to find out whether the use of interactive multimedia is effective in improving students' vocabulary achievement and to find out students' responses toward the use of interactive multimedia. This study employs a quasi experimental with nonequivalent groups design and data are collected through administering pre-test, post-test, and interview. The samples consist of two classes of the seventh grade of junior high school students; one as experimental and one as control group. The experimental group is treated by interactive multimedia, whereas the control group is treated by conventional method. The findings of the study reveal that the use of interactive multimedia is effective in improving students' vocabulary achievement. Furthermore, there are some positive students' responses toward the use of interactive multimedia evoked: facilitating students' to learn vocabulary, increasing students' motivation, and creating creative thinking. In accordance to the result of the study, the study yields the conclusion that interactive multimedia treatment is appropriate to be used as alternative technique in teaching vocabulary. It is then suggested that interactive multimedia is recommended to be applied in teaching vocabulary and teachers who apply this technique should be able to select the interesting and relevant material which appropriate with students' needs and characteristics. Besides, the teachers also should be able to design the materials precisely and deliver them interestingly to the students.